(untitled) (E Global Congress, 2025)
This article presents analytical expressions that make it possible to determine the exit time of dispersed materials from a perforated drum that sorts such materials. The expressions are derived based on the movement of the material along the length of the drum during the sorting process. The calculated results have been solved and analyzed numerically using Microsoft Excel.